PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM MELALUI KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE DI BEI - Riani, Ririn; Rinaldo, Dito (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Abstract Global economic growth is declinining amidst a decline in people’s purchasing power, resulting in declining profitability level and plummeting stock prices. This study aims to examine the effect of profitability (ROA) on dividend policy (DPR) and stock prices in food and beverage sub-sector manufacturing companies listed on the IDX in 2019-2023. The method used is a descriptive and verification method with secondary data sourced from financial reports and annual stock price reports. The population in this study were food and beverage companies listed on the IDX in 2019-2023. The sampling technique used a purposive sampling technique with a sample of 18 companies. The data analysis technique used is Path Analysis using SPSS. The results of the study show that profitability (ROA) has a positive effect on stock prices, and profitability (ROA) does not affect stock prices through dividend policy (DPR) in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. Keyword: Profitability, Dividend Policy, Stock Price